The Effect of Tibial Plateau Levelling Osteotomy on Stifle Extensor Mechanism Load: A Canine Ex Vivo Study - Drew, Jarrod O.; Glyde, Mark R.; Hosgood, Giselle L.; Hayes, Alex J. (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objective To evaluate the effect of tibial plateau levelling osteotomy on stifle extensor mechanism load in an ex vivo cruciate-intact canine cadaveric model.Study Design Ex vivo mechanical testing study.Animals Cadaveric canine pelvic limbs (n = 6).Materials and Methods A 21-mm tibial radial osteotomy was performed on pelvic limbs (n = 6) prior to being mounted into a load-bearing limb press. The proximal tibial segment was incrementally rotated until the anatomical tibial plateau angle had been rotated to at least 1°. The proportional change in stifle extensor mechanism load between the anatomical tibial plateau angle and the neutralized (∼6.5 degrees) and over-rotated (∼1°) tibial plateau angle was analysed using a one-sample t-test against a null hypothesis of no change. A p-value ≤0.05 was considered significant.Results There was no significant change in the stifle extensor mechanism load from the anatomical tibial plateau angle (308 N [261–355 N]) to the neutralized tibial plateau angle (313 N [254–372 N]; p =.81), or from the anatomical tibial plateau angle to the over-rotated tibial plateau angle (303 N [254–352 N; p = 0.67).Conclusion Tibial plateau levelling osteotomy does not significantly alter stifle extensor mechanism load at either a neutralized or over-rotated tibial plateau angle in our cruciate-intact model.
Keywords: cruciate ligament disease; TPLO; biomechanics; dog; canine